2020
DOI: 10.18203/2349-3291.ijcp20202129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TOPS score as predictor for outcome in sick newborns

Abstract: Background: Multiple parameters have been developed to prognosticate the outcomes of critically ill newborns admitted in NICUs. The objective of this study is to predict the outcome of newborns admitted in NICU using a simple but efficient score, TOPS score, involving alteration of physiological parameters. Aim of this study was to evaluate role of TOPS score in predicting mortality in sick neonates.Methods: The variables assessed under TOPS score on arrival for all subjects were: Temperature, Oxygen Saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Only 33% of our neonates were found to be hypoxic which closely matches studies conducted by Pathak et al 9 (27.8%), Begum et al(28.2%), 13 Sheth M.N. et al(29.5%) 14 while 51.6% were hypoxic in the study by Bagel et al 8 Perfusion as per prolonged CRT was found deranged in 43% of our study population and it matches with Pathak et al 9 33.9%, while rest of the studies reflect a much better state of perfusion of the babies on arrival. The issue of hypoglycaemia again is higher in our neonates(17.6%) almost matching the 22% in Pathak et al 9 study, while remain a long way from the single digit proportions of our other compared studies.…”
Section: Discussionsupporting
confidence: 89%
“…Only 33% of our neonates were found to be hypoxic which closely matches studies conducted by Pathak et al 9 (27.8%), Begum et al(28.2%), 13 Sheth M.N. et al(29.5%) 14 while 51.6% were hypoxic in the study by Bagel et al 8 Perfusion as per prolonged CRT was found deranged in 43% of our study population and it matches with Pathak et al 9 33.9%, while rest of the studies reflect a much better state of perfusion of the babies on arrival. The issue of hypoglycaemia again is higher in our neonates(17.6%) almost matching the 22% in Pathak et al 9 study, while remain a long way from the single digit proportions of our other compared studies.…”
Section: Discussionsupporting
confidence: 89%
“…Normal saturation on arrival (≥ 90%) was significantly associated with higher chances of survival (62% vs 16.7%, p =0.04). Studies by Sheth and Pandya, 12 Ayesha Begum et al, 13 and Chedda et al 14 found similar findings in their study as well where hypoxia on arrival was associated with higher chances of mortality.…”
Section: Discussionsupporting
confidence: 74%
“…CRT of <3 seconds on arrival was significantly associated with more chances of survival (80% vs 33.3%, p =0.013). Sheth and Pandya 12 conducted a study where they evaluated the outcome of sick newborns using Temperature, oxygenation, capillary refill time (perfusion), and blood sugar score and found that the maximum odds for mortality was observed with poor perfusion (odds ratio = 33.406 with a p value < 0.05). Delayed CRT is a marker for poor perfusion and can be due to multiple reasons such as hypovolemia, peripheral vasodilatation, and decreased cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…The instruments used for measuring the TOPS are of standard and calibrated by the manufacturer. The instruments used for measuring TOPS score are as follows, Temperature measured by the Omron digital thermometer, Oxygen saturation by Masimo pulse oximeter, Blood sugar was evaluated by Dr Morepen Gluco one Glucometer, Perfusion done through the clinical assessment by testing over sternum/sole [ 11 , 14 ]. Figure 1 represents the aetiology of referral in detail.…”
Section: Methodsmentioning
confidence: 99%
“…The variables which are used for the scoring purpose are less susceptible to subjective variation and each variable has an independent risk associated with mortality. On the other hand, the TOPS scoring method demands large population size when compared to SNAP II and do not consider the perinatal factors [ 8 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%